(untitled) (Pubmet, 2025)
Open science promotes transparency, open access, and reproducibility in research, ensuring that research outputs are openly available and reusable by others. However, traditional research assessment systems usually emphasize quantitative indicators, such as journal impact factors and citation counts, encouraging publication in ‘high-prestige’ journals and failing to fully capture the value of open science practices. Accordingly, a Current Research Information System (CRIS) tracking research outputs for assessment purposes does not necessarily encourage open science practices. This presentation explores the challenges and strategies involved in reconciling open science practices with research assessment requirements in Serbia during the process of establishing the national CRIS system eNauka.